EDUCATION IN THE FIELD OF CLIMATE CHANGE ADAPTATION AS AN INTEGRAL PART OF ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Oksana Liuta; Ivan Tymchuk; Myroslav Malovanyy; Tsitsino Turkadze (Environmental Problems, 2024)
Every year, the problem of globalisation of environmental challenges is becoming more and more noticeable, with climate change taking priority place among them. The lack of a sufficient number of climate-related disciplines in Ukrainian educational institutions limits the number ofenvironmentalexperts who will be able to effectively implementclimate change adaptation measures and implement the world's best practices in reducing greenhouse gas emissions through decarbonisation of energy, implementation of energy-saving equipment and transition from fossil fuels to renewable energy sources. It has been determined that in recent decades the number of scientific publications focused on the development of educationalprocesses in the context of climate change has increased rapidly. It has been found that the main directions of implementing climate education in educational institutions are to provide quality school education to rethink the priorities of an environmentally friendly lifestyle and to form highly qualified specialists at universities who will be able to implement climate change adaptation projects in various sectors of theeconomy after obtaining a quality and holistic education at universities.